2006
DOI: 10.1590/s1678-58782006000100005
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable fibrous thermal insulation

Abstract: Biodegradable Fibrous Thermal Insulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 3 publications
(2 reference statements)
0
22
0
1
Order By: Relevance
“…This article discusses the manufacture of thermal insulation from agricultural waste, thus creating a useful building material [10,11]. Coconut husk and bagasse were considered to be the raw materials offering greatest potential for manufacture of thermal insulation [12], particularly in the context of Thailand [13]. This is because these raw materials are available within Thailand, and reducing the transportation component of embodied energy gives the potential for an improved environmental profile compared with those that are imported from overseas.…”
Section: Introductionmentioning
confidence: 99%
“…This article discusses the manufacture of thermal insulation from agricultural waste, thus creating a useful building material [10,11]. Coconut husk and bagasse were considered to be the raw materials offering greatest potential for manufacture of thermal insulation [12], particularly in the context of Thailand [13]. This is because these raw materials are available within Thailand, and reducing the transportation component of embodied energy gives the potential for an improved environmental profile compared with those that are imported from overseas.…”
Section: Introductionmentioning
confidence: 99%
“…The 75% paper oil palm particle board shows slightly lower thermal conductivity 0.04158 W/mK at mean temperature of 20 o C compare to pure oil palm fiber particle board. According to previous study [11,12], it found that the materials that containing cellulose or so-called lignocellulosic fiber are good in acoustic and thermal insulation. Beside the oil palm fiber, paper is another lignocellulosic material that containing cellulose and it is the easiest materials that can be obtained.…”
Section: B Thermal Propertiesmentioning
confidence: 99%
“…Prior to the determination of thermal conductivity, thermal history of individual material was determined. The thermal conductivity tests ( Figure 7) was conducted in line with ASTM E1530-11 (Eeday et al, 2014;Rodriguez et al, 2011;Zhou et al, 2010;Satta & Steve, 2008;Manohar et al, 2006). The thermal properties of the materials were established using steady-state, one-dimensional condition.…”
Section: Determination Of Thermal Conductivitymentioning
confidence: 99%